2009
DOI: 10.1177/1043986209335015
|View full text |Cite
|
Sign up to set email alerts
|

Considering the Gendered Nature of Constrained Behavior Practices Among Male and Female College Students

Abstract: Previous research suggests that individuals engage in a variety of constrained behaviors to protect themselves from potential victimization. Although research controls for gender and constrained behaviors in fear of crime models, few studies consider constrained behaviors through a gendered lens. Using university survey data as an exploratory case study, this article hypothesizes that men and women use different types of constrained behaviors and, using factor analysis, constructs a gender-sensitive typology o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
30
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 37 publications
1
30
0
Order By: Relevance
“…The topic is of consequencefear of crime is associated with constrained behavior (Ferraro, 1995;Liska, Sanchirico, & Reed, 1988), and many argue that fear of crime's restrictive consequences are greater for women (Gordon & Riger, 1989;Madriz, 1997;Rader, Cossman, & Allison, 2009;Scott, 2003;Stanko, 1992). The topic is of consequencefear of crime is associated with constrained behavior (Ferraro, 1995;Liska, Sanchirico, & Reed, 1988), and many argue that fear of crime's restrictive consequences are greater for women (Gordon & Riger, 1989;Madriz, 1997;Rader, Cossman, & Allison, 2009;Scott, 2003;Stanko, 1992).…”
mentioning
confidence: 99%
“…The topic is of consequencefear of crime is associated with constrained behavior (Ferraro, 1995;Liska, Sanchirico, & Reed, 1988), and many argue that fear of crime's restrictive consequences are greater for women (Gordon & Riger, 1989;Madriz, 1997;Rader, Cossman, & Allison, 2009;Scott, 2003;Stanko, 1992). The topic is of consequencefear of crime is associated with constrained behavior (Ferraro, 1995;Liska, Sanchirico, & Reed, 1988), and many argue that fear of crime's restrictive consequences are greater for women (Gordon & Riger, 1989;Madriz, 1997;Rader, Cossman, & Allison, 2009;Scott, 2003;Stanko, 1992).…”
mentioning
confidence: 99%
“…The author suggests that this may be due to the residents' perception of future property crime risk increased. Other work suggests that perceived levels of crime, fear of crime, and crime-related problems are associated with neighborhood dissatisfaction and a desire to move (Skogan 1990a;Skogan and Maxfield 1981), and that individuals may alter their routine activities or adopt various protective measures in response to a perceived threat of victimization (Keane 1998;Rader, Cossman, and Allison 2009;Rountree and Land 1996). A survey of residents who had recently moved found that an important reason listed for the choice of a new neighborhood was the crime level and relative safety (Percy, Hawkins, and Maier 1995).…”
Section: Crime and Residential Mobilitymentioning
confidence: 99%
“…Avoidance behaviors include limiting daily activities or avoiding places or events, while protective behaviors include such things as owning a weapon, buying a watch dog, or taking a self defense class (Ferraro and LaGrange 1987). A widely used constrained behavior scale of 10 avoidance and protective items developed by Ferraro and LaGrange (1987) has been updated by more recent researchers who add measures to make it more current (e.g., Fisher et al 1994;Fisher and Sloan 2003;Rader et al 2009;Warr and Ellison 2000).…”
Section: Constrained Behaviorsmentioning
confidence: 99%